2017
DOI: 10.4274/jtgga.2017.0022
|View full text |Cite
|
Sign up to set email alerts
|

Does size matter? Retrospective analysis of large gynecologic tumors

Abstract: Objective:To evaluate the characteristics of patients who underwent surgery due to the presence of a large pelvic-abdominal mass over a 5-year period in a university clinic.Material and Methods:Among 3476 gynecologic operations, intraoperative findings were evaluated retrospectively. Uterine and/or adnexal masses smaller than 20 cm were excluded to refine “large” tumors and 74 patients with large tumors were enrolled in the study group. Demographic characteristics, intraoperative findings, and results of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(24 reference statements)
0
5
3
Order By: Relevance
“…One of the important factors against the suggestion of laparoscopic surgery for large adnexal masses is the risk of rupture and its negative effect on patients' outcomes (7,8). However, in our study, incidental rupture was only observed in 8 patients, two of whom were malignant.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…One of the important factors against the suggestion of laparoscopic surgery for large adnexal masses is the risk of rupture and its negative effect on patients' outcomes (7,8). However, in our study, incidental rupture was only observed in 8 patients, two of whom were malignant.…”
Section: Discussioncontrasting
confidence: 59%
“…Another important factor for the choice of laparoscopic or laparotomic management of adnexal masses is the size of the mass, and due to the technical di culty of performing laparoscopy, limited surgical eld, and the higher probability of malignant potential in adnexal masses, some suggest the use of laparotomy in large adnexal masses (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Even the ultrasound report was that of a likely mucinous cystadenoma, which are usually large and benign. It has been noted in the literature that benign and borderline tumours are more common among large abdominopelvic masses, although the presence of ascites and elevated CA 125 may present malignancy in large gynaecologic tumours, 6 which were not seen in our case.…”
Section: Resultscontrasting
confidence: 43%
“…Imaging and calculating RMI is a massive ovarian tumor is another difficult work due to poor visibility of adjacent intra-abdominal organs and only the mass can be visualized. 5 However, consistency and septation can be evaluated well, though the size and origin may often be disguised. Computed tomography scan may be superior for evaluating the status of the retroperitoneal lymph nodes only.…”
Section: Discussionmentioning
confidence: 99%